Implementasi Program KKN Gerakan Pangan Murah untuk Meningkatkan Akses Pangan dan Kesadaran Gizi Masyarakat di Kecamatan Lubuk Dalam, Kabupaten Siak, Provinsi Riau - Nadya Putri Auliya Serawaidi; Dwi Yana Rahmadilla; Fadhly Akbar; Gloria Leluri RFC; Innaya Iqlima Wanda Putri; Nur Sri Rejeki; Neila Amalina; Rifqah Khairunnisa; Reni Nurfahizah; Yuli Noviani; Wardatuzzakia Wardatuzzakia (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2025)
The Cheap Food Movement (Gerakan Pangan Murah / GPM) is a government initiative aimed at ensuring the availability of affordable basic food commodities while simultaneously increasing public awareness of balanced and healthy nutrition. This study describes the implementation of the GPM program carried out by KKN 04 students from Universitas Abdurrab in Lubuk Dalam Subdistrict, Siak Regency, Riau Province, on August 30, 2025. The research employed a qualitative descriptive approach to capture the dynamics of program implementation, with a focus on food distribution mechanisms, nutrition education activities, and patterns of interaction between students and the local community. Data were obtained through direct observation, documentation, and participation in program activities. The results indicate that the distribution of 300 food packages was conducted efficiently and reached the targeted beneficiaries. In addition, nutrition education sessions were well received by residents, reflecting a high level of community participation and interest. These activities contributed to increased awareness of healthy eating habits and the importance of balanced nutrition. The KKN 04 students played a strategic role as intermediaries between government programs and community needs. Overall, the GPM program provided tangible economic relief and positive health-related impacts for local residents.